Presentation 1_Building regulatory resilience in shipping: green technology licensing and carbon tax policies.pdf - Ying Shi (115282) (2025)
As global concerns over carbon emissions intensify, regulators worldwide have implemented diverse carbon tax policies, each shaped by specific environmental objectives and economic considerations. In response, shipping carriers have increasingly invested in Research and Development (R&D) or purchased low-carbon technologies to comply with varying regulatory standards and maintain market competitiveness. Against this backdrop, this study develops game-theoretic models to analyze optimal technology licensing strategies for shipping carriers holding carbon-reduction technology in a competitive market. It further examines how regulators can set appropriate carbon tax levels to influence licensing behaviors under different policy objectives. Our findings reveal that when the implementation costs of the green technology are manageable, sole licensing can effectively align regulatory goals with carriers’ profit objectives. However, as costs increase, the patentee carrier may gradually prefer licensing strategies that restrict the technology adoption to only the carrier with lower initial carbon efficiency, deviating from the regulator's intended outcome. If the regulator's goal is to maximize the adoption of green technology, it can realign incentives or achieve suboptimal outcomes by lowering carbon taxes or offering subsidies. Conversely, if the regulator is more focused on social welfare, the most robust choice is to set the tax at a level that maximizes welfare under sole licensing conditions. Finally, we find that providing carbon tax discounts to carriers implementing green technology does not alter the decision structure but can amplify the advantages of sole licensing, resulting in higher social welfare.